2009
DOI: 10.1007/s12038-009-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome analysis of cervical intraepithelial neoplasia and cervical squamous cell carcinoma

Abstract: Although cervical cancer is preventable with early detection, it remains the second most common malignancy among women. An understanding of how proteins change in their expression during a particular diseased state such as cervical cancer will contribute to an understanding of how the disease develops and progresses. Potentially, it may also lead to the ability to predict the occurrence of the disease. With this in mind, we aimed to identify differentially expressed proteins in the plasma of cervical cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Several of the proteins found in this study have been reported by others in cervical mucus samples [26], and also in plasma samples from patients with CIN [28] or in cervical tissue samples [29-32]. Vimentin was found down-regulated in vaginal and cervical carcinoma compared to normal tissue [31,32].…”
Section: Discussionsupporting
confidence: 79%
“…Several of the proteins found in this study have been reported by others in cervical mucus samples [26], and also in plasma samples from patients with CIN [28] or in cervical tissue samples [29-32]. Vimentin was found down-regulated in vaginal and cervical carcinoma compared to normal tissue [31,32].…”
Section: Discussionsupporting
confidence: 79%
“…6 CLU expression is complex, as the protein appears as an 80 kDa secretory form (sCLU), composed of 40 kDa alpha and beta subunits, and a $55 kDa nuclear form (nCLU). 7 CLU has been implicated in various physiological processes and in many severe physiological disturbance states including ageing, cancer progression, vascular damage, diabetes, kidney, and neuron degeneration. 8 Indeed, numerous functions have been assigned to CLU such as complement inhibition, antiproliferating factor, apoptosis, negative regulator of matrix metalloproteinase, chaperone, and cell-cell or cell-substratum interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is associated with tumor invasion and metastasis via plasminogen activation, leading to extracellular proteolysis (Clemmensen et al, 1986;Obrist et al, 2004;Danø et al, 2005;Dai et al, 2019). Furthermore, CLEC3B has been identified in various oncological pathologies, including breast, bladder, cervical, and ovarian cancers, melanoma, and gastric adenocarcinoma (Verspaget et al, 1994;Arvanitis et al, 2002;Brunner et al, 2007;Looi et al, 2009;Zhang et al, 2017). Although CLEC3B levels have been reported to decrease in patients with HCC, its specific role and associated tumorigenesis mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%